2002
DOI: 10.1016/s0020-7292(02)00227-8
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section as a cause of chronic pelvic pain

Abstract: In the present study cesarean section was associated with chronic pelvic pain. This fact may be the cause of a public health problem in the coming years, due to the raised rates of cesarean section in Brazilian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0
11

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(62 citation statements)
references
References 6 publications
3
48
0
11
Order By: Relevance
“…However, CS has been suggested as a cause of chronic (intra-) pelvic pain [3]. Results from the present cohort have been reported elsewhere and the prevalence of persistent LBPP after pregnancy was previously estimated to be 43% [14][15][16][17].…”
supporting
confidence: 64%
“…However, CS has been suggested as a cause of chronic (intra-) pelvic pain [3]. Results from the present cohort have been reported elsewhere and the prevalence of persistent LBPP after pregnancy was previously estimated to be 43% [14][15][16][17].…”
supporting
confidence: 64%
“…Various studies have confirmed that there is higher incidence of PPH, postpartum infection, chronic abdominal pain, rehospitalisation after elective caesarean section performed in nulliparous low risk women compared to that after vaginal delivery [27][28][29]. Babies are also vulnerable to unnecessary risks from rising CS rates.…”
Section: Associated Risksmentioning
confidence: 99%
“…When comparing NVD and CS, Torkan et al, found those with NVD reported higher marks in all areas assessing quality of life except "satisfaction towards delivery". They concluded that CS did not improve the quality of life for the mother postpartum [14].…”
Section: Introductionmentioning
confidence: 98%
“…Almeida et al, (2002) in a study of 199 women found that 67.2% of women experiencing chronic pelvic pain had a history of CS [10]. Fabris et al, (2011) concluded that chronic pelvic pain was more relevant after a CS compared to NVD, although pelvic pain is common with both [11].…”
Section: Introductionmentioning
confidence: 99%